2013
DOI: 10.3233/ch-131686
|View full text |Cite
|
Sign up to set email alerts
|

Exercise hemorheology: Moving from old simplistic paradigms to a more complex picture

Abstract: Classic studies on exercise hemorheology evidenced that blood fluidity is impaired during exercise (short term exercise-induced hyperviscosity) and is improved as a result of regular exercise practice (hemorheologic fitness). Extensive description of these events led to the concepts of "the triphasic effects of exercise", "the paradox of hematocrit", and "the hemorheological paradox of lactate". However, some results obtained in training studies do not fit with this classical picture and cannot be explained by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
18
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 80 publications
4
18
0
1
Order By: Relevance
“…Rheological properties of blood are highly affected by exercise training. A "triphasic" action of exercise on blood rheology has been proposed [75,76]. It is reported that short-term effect of exercise is an increase in blood viscosity, mostly due to a rise in hematocrit and plasma viscosity induced either by fluid shift, water loss, and release of sequestered RBCs from spleen or water trapping in muscle [76][77][78].…”
Section: Exercise-induced Shear Stress Rheological Properties Of Blomentioning
confidence: 99%
See 4 more Smart Citations
“…Rheological properties of blood are highly affected by exercise training. A "triphasic" action of exercise on blood rheology has been proposed [75,76]. It is reported that short-term effect of exercise is an increase in blood viscosity, mostly due to a rise in hematocrit and plasma viscosity induced either by fluid shift, water loss, and release of sequestered RBCs from spleen or water trapping in muscle [76][77][78].…”
Section: Exercise-induced Shear Stress Rheological Properties Of Blomentioning
confidence: 99%
“…A "triphasic" action of exercise on blood rheology has been proposed [75,76]. It is reported that short-term effect of exercise is an increase in blood viscosity, mostly due to a rise in hematocrit and plasma viscosity induced either by fluid shift, water loss, and release of sequestered RBCs from spleen or water trapping in muscle [76][77][78]. Likewise, alterations in functional characteristics of erythrocytes have been shown [77,79,80].…”
Section: Exercise-induced Shear Stress Rheological Properties Of Blomentioning
confidence: 99%
See 3 more Smart Citations